Pembuatan Biodiesel dari Minyak Kemiri Sunan dengan Proses Dua Tahap - Sri Wahyu Murni; Geoshinta Kusumawardani; Thea Arifin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Sunan Hazelnut is one plant that thrives in Indonesia and  have high productivity is 50-300 kg per tree per year, with oil content of 45-55%, so it very potential to be used as raw material for biodiesel production. Sunan Hazelnut oil can not be converted directly into biodiesel because the free fatty acid (FFA) content is high. To overcome this problem, a two-stage process can be conducted. The first stage  aims to reduce the content of FFA in oils through esterification reaction using an acid catalyst, the second stage is the production of biodiesel through transesterification using alkaline catalyst. In this study, the esterification reaction is carried out in certain condition. The variables being studied is the effect of the concentration of NaOH catalyst and time of the transesterification reaction. The results shows that the FFA content can be reduced to 0.55% using sulfuric acid catalyst 0.5% by weight of oil, oil to methanol ratio of 1:5 and a reaction time of 120 minutes. Then, oil is converted into biodiesel using NaOH catalyst, obtained a conversion of 83% on the amount of catalyst 0.75% by weight of oil, methanol to oil ratio of 1:7 and a reaction time of 90 minutes. Biodiesel produced has a density of  875 kg /m3, 2.35 cst of viscosity, flash point   of 163oC  and pour point of -2,5oC.